SINKRONISASI KEWENANGAN PENYELENGGARAAN URUSAN DI BIDANG KEHUTANAN - Gatot Dwi Hendro Wibowo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Though have taken place five year implementation the Act No. 22/1999 (improved by Act No. 32/2004), still be potential generate insist uncompromisingly or